Economics of Philippine mining rents, price cycles, externalities, and the uncompensated costs - Bautista, Germelino M. (2009)
This paper argues that the country's current strategy of commodity. trade "niche-ing" via mineral production is threat to sustainable development, and hardly a program of economic growth. Given the enclave character of the metallic mineral industry, its capital-intensive production, the small income shares for labor, the indigenous people, and the environment, and the greater share of rent fully remitted out of the country without contributing to domestic capital accumulation, the strategy's impact of growth is insignificant. also government's remedial measures and funding programs with mining contractors to address the negative externalities of mining would not fully mitigate the negative resource and environmental impacts, nor provide adequate compensation of the adverse economic and social costs. The estimated amount of mitigation measures and damage compensations would hardly cover the costs of community displacements, the loss of local clean water supply, and the health and and livelihood damages from pollution and collapse of tailing dams. Three policy measures are proposed to address these contradictions.
Keywords: Mining; Sustainable development -- Philippines; Environmental policy -- Philippines